PENYULUHAN HUKUM DALAM UPAYA PENINGKATAN KESADARAN HUKUM BERLALULINTAS MELALUI PEMAHAMAN TERHADAP ISI UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Sudjana, Sudjana (Universitas Pendidikan Indonesia, 2016)
This study discusses the public understanding of the contents of Law No. 22 of 2009 regarding Traffic and Road Transportation. This is important, considering traffic and road transportation has an important role to realize the security, prosperity, order traffic and road transportation to support economic development. Methods Research method used is a normative juridical approach, Specifications descriptive analytical research, conducted research stage through the study of literature to examine the primary legal materials, secondary law, and tertiary legal materials. Data collected through the study of documents, and the method of data analysis is done through qualitative normative. The results showed that the understanding of the contents of Law No. 22 of 2009 regarding Traffic and Road Transportation is difficult to measure the level of legal awareness of citizens because there are other factors that affect the example of officials and oversight mechanisms in determining well.Keywords: legal education, legal awareness, understanding, traffic and road transportation law.